Dynamics and Diagnosis of Independent Thinking Processes of Students (on the Example of the First Teenagers) - Buriyeva, Kibrio; Omonovich, Khimmataliev Dustnazar (Journal of Education for Sustainability and Diversity, 2024)
The article describes, creative, modular technologies for improving the socio-psychological mechanisms of the development of independent thinking of adolescent students are included in the practice. The following methodologies were used, which were considered subtests of the scientific and theoretical sources on the topic, comparative analysis, observation, question and answer, conversation, Wexler and Amtxauer methodologies: methodology "separation of important characters", methodology "quantitative relations", methodology of "intellectual disability", methodology "complex analogy", conducting training sessions on advanced pedagogical technologies in order to determine the psychological impact,generalization of mathematical-statistical results in order to prove the scientific value of empirical materials.  Theoretical and practical significance of the study: scientific-theoretical justification of the problem of independent thinking of adolescents; identification of its specific psychological and pedagogical characteristics; identification of the content, forms and methods of independent thinking of adolescents, the development of its holistic system; development of criteria aimed at determining effective forms of independent thinking of adolescents, as well as scientifically based conclusions and recommendations on The practical significance of the study is that the ideas advanced in it can be used in the study of general secondary education schools “sense of Homeland”, “literature” (grades 5-6) educational subjects, a special course “independent thinking of adolescents”, Physical Education, Higher and secondary specialized vocational education institutions, teachers ' training and retraining institutes “pedagogy”, “psychology of young Times”.